Determination of Islet Viability Using a Zinc-Specific Fluorescent Dye and a Semiautomated Assessment Method. Issue 10 (October 2016) - Komatsu, Hirotake; Omori, Keiko; Parimi, Mounika; Rawson, Jeffrey; Kandeel, Fouad; Mullen, Yoko
Islet transplantation is an effective therapy that allows the achievement of insulin independence in patients with type 1 diabetes (T1D). To ensure successful transplantation, islet viability and function are of great importance. Viability assessments most often use fluorescein diacetate (FDA)/propidium iodide (PI) staining. However, results using this method often do not correlate well with graft function. Because FDA nonspecifically penetrates all cells present in the islet preparation, including islets and contaminating acinar cells, its use often complicates viability assessments of the overall cell population. Furthermore, the manual method for determining viability percentages is highly subjective. Shortcomings of the conventional islet viability assay can be potentially improved by staining cells with Newport Green (NG). NG, is a zinc-specific fluorescent dye that specifically reacts with zinc-rich β cells. Two kinds of NG dyes, NG-DCF and NG-PDX, are currently available. We examined the zinc specificity of these NG dyes and compared NG staining with traditional FDA staining to explore the potential of NG dyes to improve islet viability assessment. Of the two NGs tested, NG-DCF showed the higher specificity toward a β-cell line as well as human islets. NG-DCF accurately identified the islet area, even in low-purity islets, while neither FDA nor NG-PDX did. Although NG-DCF staining required a longer incubation time, the addition of poloxamer F127 and incubation at 37°C allowed viability assessment to take place within 30 min. Unlike FDA/PI staining, NG-DCF/PI staining allowed for islet-specific assessment. We also introduced a semiautomated measurement to determine NG-DCF/PI staining results, which enabled us to obtain objective and reproducible results. NG-DCF/PI staining is easy and reliable, and this method permits highly objective islet-specific viability assessments.